2019
DOI: 10.1177/1350506819831394
|View full text |Cite
|
Sign up to set email alerts
|

‘I think in some way you’re afraid to lose your dignity maybe’: Exploring Danish girls’ concerns in relation to sexual activity

Abstract: This article explores the issue of girls’ concerns about sexual activity in a liberal Nordic context. Drawing on ethnographic fieldwork among young people in Denmark, the article identifies three types of concerns girls can have about sexual activity: social expectations, relational expectations and dignity. Whilst contemporary research has tended to focus on the influence different sexual morality discourses have in shaping different expectations and concerns about these, little attention seems to be paid to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Furthermore, their most intimate experiences and feelings referred to insecurities about their bodies [34] and problems being assertive with men and refusing practices they disliked. Johansen et al [35], in their study with Danish women, found a concern among participants about being judged negatively if they did not show a liberal approach to sex; they worried about being called "boring" or "prudish".…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, their most intimate experiences and feelings referred to insecurities about their bodies [34] and problems being assertive with men and refusing practices they disliked. Johansen et al [35], in their study with Danish women, found a concern among participants about being judged negatively if they did not show a liberal approach to sex; they worried about being called "boring" or "prudish".…”
Section: Discussionmentioning
confidence: 98%
“…In turn, this fosters toxic and abusive dynamics, including those taking place in nightlife contexts (Duque et al, 2020). Thus, predatory capital has seen in the CDD a niche market, promoting practices and contexts aligned with it that contribute to its domination, despite this being at the expense of people's wellbeing (Johansen et al, 2019;Puigvert et al, 2023). Through these practices, this form of capital has fostered the idea that sexual-affective relationships are disposable, promoting a throwaway culture linked to ugliness in sex.…”
Section: Beauty and Ugliness In Sex: Where Do Profits Lie?mentioning
confidence: 99%
“…There is a double standard regarding alcohol consumption in women since male drunkenness is accepted while female drunkenness is condemned (57) due, in part, to imbalanced gender-specific consumption norms and social sanctions attributed to women who consume alcohol (55). Furthermore, women who consume alcohol excessively tend to be judged as promiscuous and unfaithful, whereas men who consume this substance are perceived as sexually experienced and capable (58)(59)(60).…”
Section: Double Gender Standard In Women Alcohol Consumersmentioning
confidence: 99%